Strengthening Credit Institutions for Rural Poverty Alleviation - Gilberto M. Llanto; Maria Teresa Sanchez-Robielos (Philippine Institute for Development Studies (PIDS), 1998)
Innovation in credit programs has alleviated poverty. The premise is that credit accessibility translates into productive activities that aid households to battle poverty. Despite this, the formal rural lending institutions are meeting only a very small percentage of the rural demand for credit. The objective of this study is twofold: to present the current status of rural credit markets, rural credit institutions and the poverty situation and to recommend measures to strengthen existing and potential rural credit institutions.
Keywords: 330; poverty alleviation; rural credit; credit agenda; informal financial sectors; nonbank financial institutions